2008
DOI: 10.1093/humrep/den462
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment to infertility: the role of intrapersonal and interpersonal resources/vulnerabilities

Abstract: The findings of the study highlight the merit of understanding intra- and interpersonal attributes for achieving better wellbeing outcomes. These findings would also prove valuable for researchers and practioners involved in designing and implementing psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 41 publications
5
42
1
6
Order By: Relevance
“…In particular, reasons why men do not disclose using ART to those outside of their immediate personal relationships tend to centre on shame (Lee and Chu, 2001) and fear of thoughtless comments (Throsby and Gill, 2004). This is problematic because research has shown that social support is associated with less stress (Martins et al, 2013) and less depression, and anxiety and greater positive adjustment to involuntary childlessness (Bute, 2013;Mahajan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, reasons why men do not disclose using ART to those outside of their immediate personal relationships tend to centre on shame (Lee and Chu, 2001) and fear of thoughtless comments (Throsby and Gill, 2004). This is problematic because research has shown that social support is associated with less stress (Martins et al, 2013) and less depression, and anxiety and greater positive adjustment to involuntary childlessness (Bute, 2013;Mahajan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Several factors may influence emotional reactions to infertility and fertility treatment, including sociodemographic factors and psychosocial factors, such as coping strategies (e.g., avoidance coping) (Benyamini, Gozlam, & Kokia, 2009, Gourounti, Anagnostopoulos, & Vaslamatzis, 2010a, Mahajan et al, 2009, van den Broeck et al, 2010. A review of this issue (Gourounti, Anagnostopoulos, & Vaslamatzis, 2010b) suggested that the role of psychological factors in relation to infertility stress has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the worldwide continuous increase in the numbers of ART cycles, in 2010 only 27.1% had success (Dyer et al., ). The cause for patients’ infertility are often related to an intertwining biological, lifestyle, and occupational aspects (Centers for Disease Control and Prevention, ), along with intrapersonal, interpersonal, and environmental factors (Mahajan et al., ). As so, a holistic and integrated nursing approach to these patients is required (Romeiro, Caldeira, Brady, Hall, & Timmins, ; Romeiro, Caldeira, Brady, Timmins, & Hall, ).…”
mentioning
confidence: 99%